Resíduos Sólidos Recicláveis Gerados na Universidade Federal Rural do Semi-Árido campus Pau dos Ferros - Almeida, Raianny Mikaelly Melo de (Universidade Federal Rural do Semi-Árido, 2019)
The intense generation of solid waste and their improper final destination is one of the major problems that is being faced in present-day society. Several institutions have been generating large quantities of solid waste,, as is the case in universities, due to the great flow of people in constant circulation in this environment. However, the present study aims to carry out a exploratory survey of the recyclable solid waste generated at the Universidade Federal Rural do Semi-Árido, Campus Pau dos Ferros-RN, having as specific objectives: to characterize and quantify the generation of recyclable solid waste; to identify and evaluate the temporary storage containers of this waste on campus and then, check the perceptions and attitudes adopted by the university community before the issue, thereby contributing to the efficient implementation of selective collection at university. For the quantification and qualitative characterization of the recyclable solid waste generated, ten samples of properly separated waste were weighed according to their physical properties, their origin and proper final destination, so that they were separeted into metal, paper / cardboard, plastic and glass. The stage corresponding to environmental education was conducted based on the data collection, by means of an instrument such as questionnaire type applied to Campus community. Regarding the characterization, considering the average percentage values measured for all samples from August 9, 2018 to February 7, 2019, it was verified that the paper / cardboard contributed with approximately 75.0%, the plastic with 17.0%, the glass with 5.0% and finally the metal with 3.0%. For the quantitative values, based on the performed weighings, showed an average production of recyclable solid wastes of 13.490 kg/day. According to the survey of the number of existing containers and the daily estimate for the generation of recyclable solid waste, the institution must acquire 08 containers with a capacity of 200 L for external temporary storage of the recyclable solid waste generated on campus. Through the answers obtained through the questionnaire, it was possible to visualize that environmental education is an important issue to be approached continuously by the various sectors of society, being the university one of the places in which this theme should be worked, in order to awaken the critical sense of all its population, as well to sensitize them with respect to the practices of conservation and preservation of the environment in which they live. In addition, it could be verified that the present study is of great relevance for the updated data provision corresponding to the generation of recyclable solid waste on campus. Therefore, UFERSA Campus Pau dos Ferros should promote or improve internal policies directed to the reuse and recycling of its waste, such as training and awareness-raising actions in the community aiming to promote the sustainability scenario.
Keywords: Educação ambiental; Gerenciamento; Instituição pública; Resíduos sólidos recicláveis; Environmental education; Management; Public institution; Recyclable solid waste; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA